Differential activation of yeast adenylyl cyclase by Ras1 and Ras2 depends on the conserved N terminus. - Hurwitz, N (1995)
Although both Ras1 and Ras2 activate adenylyl cyclase in yeast, a number of differences can be observed regarding their function in the cAMP pathway. To explore the relative contribution of conserved and variable domains in determining these differences, chimeric RAS1-RAS2 or RAS2-RAS1 genes were constructed by swapping the sequences encoding the variable C-terminal domains. These constructs were expressed in a cdc25ts ras1 ras2 strain. Biochemical data show that the difference in efficacy of adenylyl cyclase activation between the two Ras proteins resides in the highly conserved N-terminal domain. This finding is supported by the observation that Ras2 delta, in which the C-terminal domain of Ras2 has been deleted, is a more potent activator of the yeast adenylyl cyclase than Ras1 delta, in which the C-terminal domain of Ras1 has been deleted. These observations suggest that amino acid residues other than the highly conserved residues of the effector domain within the N terminus may determine the efficiency of functional interaction with adenylyl cyclase. Similar levels of intracellular cAMP were found in Ras1, Ras1-Ras2, Ras1 delta, Ras2, and Ras2-Ras1 strains throughout the growth curve. This was found to result from the higher expression of Ras1 and Ras1-Ras2, which compensate for their lower efficacy in activating adenylyl cyclase. These results suggest that the difference between the Ras1 and the Ras2 phenotype is not due to their different efficacy in activating the cAMP pathway and that the divergent C-terminal domains are responsible for these differences, through interaction with other regulatory elements.